Twentieth century political theory - Bronner, Stephen Eric (ed.) (New York, 2006)
Twentieth Century Political Theory: A Reader is a comprehensive collection that brings together the most important writings by the thinkers and political figures who have defined the canon of contemporary political thought. Stephen Eric Bronner has thoroughly revised and updated the second edition with seventeen new essays, a new extended introduction, and new sectional introductions to introduce students to the most salient and current debates over liberalism, socialism, fascism, postmodernism, feminism, postcolonialism, and a host of other important ideas.
Keywords: Political science -Philosophy